Dosimetric effect of rotational setup errors in stereotactic radiosurgery with HyperArc for single and multiple brain metastases. Issue 10 (11th September 2019) - Sagawa, Tomohiro; Ohira, Shingo; Ueda, Yoshihiro; Akino, Yuichi; Mizuno, Hirokazu; Matsumoto, Masao; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Abstract: Purpose: In stereotactic radiosurgery (SRS) with single‐isocentric treatments for brain metastases, rotational setup errors may cause considerable dosimetric effects. We assessed the dosimetric effects on HyperArc plans for single and multiple metastases. Methods: For 29 patients (1–8 brain metastases), HyperArc plans with a prescription dose of 20–24 Gy for a dose that covers 95% (D95% ) of the planning target volume (PTV) were retrospectively generated (Ref‐plan). Subsequently, the computed tomography (CT) used for the Ref‐plan and cone‐beam CT acquired during treatments (Rot‐CT) were registered. The HyperArc plans involving rotational setup errors (Rot‐plan) were generated by re‐calculating doses based on the Rot‐CT. The dosimetric parameters between the two plans were compared. Results: The dosimetric parameters [D99%, D95%, D1%, homogeneity index, and conformity index (CI)] for the single‐metastasis cases were comparable ( P > 0.05), whereas the D95% for each PTV of the Rot‐plan decreased 10.8% on average, and the CI of the Rot‐plan was also significantly lower than that of the Ref‐plan (Ref‐plan vs Rot‐plan, 0.93 ± 0.02 vs 0.75 ± 0.14, P < 0.01) for the multiple‐metastases cases. In addition, for the multiple‐metastases cases, the Rot‐plan resulted in significantly higher V10Gy ( P = 0.01), V12Gy ( P = 0.02), V14Gy ( P = 0.02), and V16Gy ( P < 0.01) than those in the Ref‐plan. Conclusion: The rotational setup errors for multiple brain metastases cases caused non‐negligible underdosage for PTV and significant increases of V10Gy to V16Gy in SRS with HyperArc.